Menelisik Jejak Pendidikan di Sulawesi Selatan: dari Sistem Pendidikan Tradisonal hingga Sistem Pendidikan Modern - Junaeda, St. (Rihlah: Jurnal Sejarah dan Kebudayaan, 2014)
This paper describes the transformation of the education system in South Sulawesi, from the model tradisioanl be modern. The education system in South Sulawesi conceptual change as a result of the ongoing colonialism. The important question is how the process of transformation of the education system in South Sulawesi. This question can pull a conclusion, that the system change from traditional to modern education is just a simple implication of an application of different interests. Far more important is the change in the education system that took place in South Sulawesi encourages the emergence of awareness in understanding the entity’s identity as a nation.